Is the G.C.E. (AL) Bio Science stream a dead end to educational opportunity in the Bio Science stream - Rupasinghe, S. (My University, 2012)
The Biological Science (Bio Science) stream had remained very popular and competitive among the subject streams offered at the General Certificate of Education, Advanced Level, as it paves the way for admission to some of the prestigious faculties in the universities. There was a clear swing towards the Science streams during the period following the lgT2curricular reforms, through which Science and Maths came to be taught in all secondary schools that had grades up to G.C.E., OL. However the trend has changed in recent years with student numbers enrolling for Science decreasing by about 16 per cent between years 1986 and 1996. This swing away from Science had been partly attributed to the highly selective and restrictive admission policies followed by the faculties concemed in the universities, amidst an increasing demand for places. The objective of this paper, therefore, is to analyse the trends prevailing in the Bio Science stream during the period, 1990 to 2000. It was revealed from the study that the number eligible for admission to universities had increased during the period concerned. However, the percentage admitted had remained low despite variations from year to year. All relevant faculties - Medicine, Science, Agriculture, Veterinary Science and Dental have foilowed very restrictive admission policies and the percentage of admissions had remained constant despite increasing pressure during the relevant period. It was also revealed that nearly 75 per cent of eligibie candidates have been annually shut off from universities. Even though a large number of females qualify for admission, the probability of a female being admitted remains at 0.23.